2012
DOI: 10.1111/j.1365-2966.2012.21993.x
|View full text |Cite
|
Sign up to set email alerts
|

The viscous evolution of white dwarf merger remnants

Abstract: We study the evolution and final outcome of long-lived (≈10 5 years) remnants from the merger of a He white dwarf (WD) with a more massive C/O or O/Ne WD. Using Modules for Experiments in Stellar Astrophysics (MESA), we show that these remnants have a red giant configuration supported by steady helium burning, adding mass to the WD core until it reaches M core ≈ 1.12 − 1.20M. At that point, the base of the surface convection zone extends into the burning layer, mixing the helium burning products (primarily car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(160 citation statements)
references
References 51 publications
6
153
1
Order By: Relevance
“…The torus density in our simulation is sufficiently low that a large fraction of 4 He may reach a sufficiently high temperature to photodissociate before burning into heavier elements. Our conclusion that He torii are unlikely to detonate is at odds with the suggestion of Schwab et al (2012) that such detonations might occur in disks created by WD-WD mergers. One possible difference in their case could be the importance of degeneracy pressure or the higher densities achieved by compression due to the presence of a WD surface.…”
Section: Implications For Wd-ns/bh Mergerscontrasting
confidence: 55%
See 1 more Smart Citation
“…The torus density in our simulation is sufficiently low that a large fraction of 4 He may reach a sufficiently high temperature to photodissociate before burning into heavier elements. Our conclusion that He torii are unlikely to detonate is at odds with the suggestion of Schwab et al (2012) that such detonations might occur in disks created by WD-WD mergers. One possible difference in their case could be the importance of degeneracy pressure or the higher densities achieved by compression due to the presence of a WD surface.…”
Section: Implications For Wd-ns/bh Mergerscontrasting
confidence: 55%
“…We thus begin our study of NuDAFs by performing hydrodynamic simulations with an anomalous viscous stress. A similar approach was adopted recently by Schwab et al (2012) in studying the evolution of accretion disks created by WD-WD mergers. In order to best evaluate the uncertainties introduced by this approach, we adopt several functional forms for the kinematic viscosity, each of which lead to different transient and quasi-steady-state outcomes.…”
Section: Angular Momentum Transportmentioning
confidence: 99%
“…As a result, carbon ignites off center even for the cases of no off-center burning in the early remnant phase. In fact, Shen et al (2012) and Schwab et al (2012) followed the evolution of merger remnants and showed that off-center carbon ignition starts in the viscous and thermal evolution phases in some cases. Yoon et al (2007) performed an SPH simulation of a CO WD merger whose mass combination was M 0.9 0.6 +  and further followed the evolution of the merger remnant with a 1D stellar evolution code.…”
Section: Remnant Phasementioning
confidence: 99%
“…In this phase, the merger remnant has not yet reached a quasi-stationary state and still has small nonaxisymmetric structures. The second phase is the viscous evolution phase (Schwab et al 2012;Shen et al 2012;Ji et al 2013), 10 4 -10 8 s after merging. In this phase, the remnant reaches a quasi-stationary, axisymmetric state and it evolves in a viscous timescale.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this evidence, the review of Hillebrandt & Niemeyer (2000) argued that the model was only viable if the accretion-induced collapse problem could be avoided. Later work by Shen et al (2012) and Schwab et al (2012) used a more detailed treatment of the viscous transport in the outer regions of the remnant and found that viscous dissipation in the centrifugally supported envelope would substantially heat up the envelope on a viscous timescale, but their simulations still led to off-center carbon burning. van Kerkwijk et al (2010) argued that equal-mass mergers would lead to the conditions necessary for carbon detonation in the center of the merged object, but Shen et al (2012) also questioned this for reasons related to how viscous transport would convert rotational motion into pressure support.…”
Section: Introductionmentioning
confidence: 99%